About General Philosophical Methods of Knowledge of Legal Phenomena and Processes - Vladimir Valentinovich Kozhevnikov (Polit Journal Scientific Journal of Politics, 2022)
In this scientific article, emphasizing the special importance in the studies of law of general philosophical methods that determine the content of the methodology as a whole, the method of existentialism is considered as one of them, which is analyzed in great detail from the standpoint of its supporters, and is also critically evaluated by modern scientists.